Mining software support tickets for assistive routing - Han, Jianglei (Nanyang Technological University, 2020)
The technical support organization of a software service provider consists of groups of experts who are processing customer tickets, which are electronic reports of any technical incident. Operationally, assigning a ticket to the correct expert is an important step towards resolution. An incorrect assignment would result in longer turnaround time and customer dissatisfaction, incurring cost and overhead.